2012
DOI: 10.1007/s10499-012-9544-2
|View full text |Cite
|
Sign up to set email alerts
|

Response of a freshwater air-breathing fish, Clarias batrachus to salinity stress: an experimental case for their farming in brackishwater areas in Andaman, India

Abstract: The study was conducted to assess the effects of salinity on growth and biochemical composition of freshwater catfish, Clarias batrachus. A static nonrenewable acute toxicity bioassay test was conducted and LC 50 of salinity for 96-h exposure to the fingerling (14.5 cm) was 12.52 %. Based on these results, two sublethal salinity levels, viz. 4 and 8 % were selected to study the long-term effects of salinity on C. batrachus for a period of 90 days. From the study, it was found that growth and survival rate were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 49 publications
6
24
0
Order By: Relevance
“…A number of experiments have been conducted to evaluate the effects of salinity levels on fish physiology to find the perfect salinity level for each fish species (Boeuf & Payan, ; Enayat, Imanpoor, Shabanpoor, & Hosseini, ). It has been reported that salinity exposure significantly affected the growth of a freshwater fish Clarias batrachus (Sarma, Prabakaran, Krishnan, Grinson, & Kumar, ). Therefore, it is important to maintain the actual level of salinity to ensure a high growth rate and lower energetic cost of osmoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experiments have been conducted to evaluate the effects of salinity levels on fish physiology to find the perfect salinity level for each fish species (Boeuf & Payan, ; Enayat, Imanpoor, Shabanpoor, & Hosseini, ). It has been reported that salinity exposure significantly affected the growth of a freshwater fish Clarias batrachus (Sarma, Prabakaran, Krishnan, Grinson, & Kumar, ). Therefore, it is important to maintain the actual level of salinity to ensure a high growth rate and lower energetic cost of osmoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in survival, growth and/or glycogen has also been reported for freshwater fish at elevated salinities (Britz & Hecht, ; Luz et al., ; Sarma, Prabakaran, Krishnan, Grinson, & Kumar, ). There was a significant reduction in liver glycogen in the liver of walking catfish ( Clarias batrachus ) when subjected to salinities of 4 and 8 ppt for 91 days, while survival and growth were both lower compared to those in freshwater (0 ppt) (Sarma et al., ). Meanwhile, there was a significant decrease in growth of C. auratus at 8 and 10 ppt and a slight, but not significant, reduction in their liver glycogen from 102.6 to 79.8 μg/mg at 0 and 10 ppt, respectively, after 21 days (Luz et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…Previous reports revealed that air-breathing fish, namely Monopterus albus (Pedersen et al 2014), Anabas testudineus , and Clarias batrachus (Sarma et al 2013), could survive in brackish water. Specifically, M. albus thrived in 10 ‰ salinity, while A. tesudineus tolerated up to 30 ‰.…”
Section: Introductionmentioning
confidence: 99%